(untitled) (Educational Dimension, 2022)
Based on the analysis of sources on the problem of research, the article defines types of electronic educational resources (EER), general requirements for them, focuses on didactic and methodological requirements and existing holistic systems of psychological and pedagogical requirements for EER, presents the main types of parameters that can be used to evaluate the quality of EER, analyzes the typical structure of EER and characterizes its components. The analysis of approaches to defining the concepts of “immersiveness”, “immersive educational environment”, “immersive approach in education”, “immersive educational resources” (IER) was carried out, on the basis of which the relationship between the virtual environment and immersive learning environment was determined, the pedagogical aspects of learning in immersive environments were considered, the classification of IER was made. The main components of IER design and implementation are analyzed, and the essence of IER design and IER design methodology is determined. In the main part of the proposed general model of the methodology of IOR design and analyzed the goals, subjects of methods, stages, and content of training, forms of organization of the educational process, methods, teaching tools, and predicted results of the methodology. In the conclusion the elements of the methodology of IЕR design are presented, in particular, a complex IЕR in the form of a distance learning course, examples of designing prototypes of immersive teaching materials, etc. are considered.